2014
DOI: 10.1016/j.chembiol.2013.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Arginyltransferase ATE1 Catalyzes Midchain Arginylation of Proteins at Side Chain Carboxylates In Vivo

Abstract: Summary Arginylation is an emerging posttranslational modification mediated by Arg-tRNA-protein-transferase (ATE1). It is believed that ATE1 links Arg solely to the N-terminus of proteins, requiring prior proteolysis or action by Met-aminopeptidases to expose the arginylated site. Here, we tested the possibility of Arg linkage to mid-chain sites within intact protein targets and found that many proteins in vivo are modified on the side chains of Asp and Glu by a novel chemistry that targets the carboxy rather … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 19 publications
1
89
0
Order By: Relevance
“…Although the a 1 ion of a dimethylated arginine was not detected in the corresponding spectra, we exclude the possibility that the identified arginylation may represent a sidechain arginylation for several reasons. First, although sidechain arginylation was detected in mouse applying the same experimental setup (29), there is to our knowledge no report on sidechain arginylation that was preceded by deamidation of a glutamine or asparagine residue into a glutamic acid or an aspartic acid residue, respectively. Second, the modified Gln 30 was the most N-terminal amino acid identified across all measurements suggesting that it was the apparent N-terminus of PpATAD3.1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the a 1 ion of a dimethylated arginine was not detected in the corresponding spectra, we exclude the possibility that the identified arginylation may represent a sidechain arginylation for several reasons. First, although sidechain arginylation was detected in mouse applying the same experimental setup (29), there is to our knowledge no report on sidechain arginylation that was preceded by deamidation of a glutamine or asparagine residue into a glutamic acid or an aspartic acid residue, respectively. Second, the modified Gln 30 was the most N-terminal amino acid identified across all measurements suggesting that it was the apparent N-terminus of PpATAD3.1.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, arginylation of glutamic acid residues can also target proteins via p62 (Sequestosome-1) binding to autophagy-mediated degradation in mammalian cell lines (27). Further, ATE-mediated arginylation can also occur on acidic side-chains of non-N-terminal amino acids (28,29). Although ATE activity was demonstrated quite early in plants (30), the functional investigation of protein arginylation in plants started only recently.…”
mentioning
confidence: 99%
“…The same group described evidence that some isoforms of R-transferase were specific for substrates bearing N-terminal Cys (93). Other recent publications by the same laboratory suggested, on the basis of MS analyses, that the Ate1 R-transferase is capable of arginylating not only ␣-amino groups of specific N-terminal residues but also ␥-carboxyl groups of internal (non-N-terminal) Asp or Glu (94,95). This suggestion followed a report, by another group, that described a modified 13-residue neurotensin hormone that A yellow oval denotes the rest of a protein substrate.…”
mentioning
confidence: 88%
“…These compartments are distinct from the currently known locations of the cytosolic/ nuclear Ate1 R-transferase (96). A subsequent publication suggested that Ate1 is capable of arginylating not only the ␣-amino groups of N-terminal residues but also ␥-carboxyl groups of internal (non-N-terminal) Asp and Glu in natural proteins and described several proteins, including actin, dystrophin, myosin, titin, and tubulin, that appeared to contain, according to MSbased data, internal Asp or Glu residues conjugated to Arg (94).…”
Section: Use Of Celluspots Assays To Address Reports About Arginylatimentioning
confidence: 99%
See 1 more Smart Citation